Journalism practice and critical reflexivity: A death in custody interview - Mason, Bonita (Pacific Media Centre, AUT University, 2014)
Critical reflexivity is a relatively recent strand in journalism studies. It has its advocates, but there are few models. This article offers one possible model, of one moment of practice: an interview with the mother-in-law of an Australian Indigenous woman who died an avoidable death in prison. The critically reflexive approach taken in this research accommodates the individual, social, objective and subjective elements in a practice, and uses the tools provided by Pierre Bourdieu's theory of practice and Donald Schon's work on reflective practice and the reflective practitioner. Together, these approaches provide different but complementary conceptual, analytical, practice-based and narrative tools for making journalism practice, and journalists in the practice, an object of study. Critical reflexivity, by adding an inside perspective, is a valid method by which to add to the range of journalism studies that examine journalism from the outside. Such research allows for an inter-weaving of context, self, others, relationships, theory, history, facts, values and experiences, expanding and enriching our understanding of journalism practice and its place in society.